A COMPARATIVE STUDY: THE IMPACT OF MICROFINANCE ON COMMUNITY WELFARE IN RURAL AND URBAN AREAS OF INDONESIA - I Nengah Suarmanayasa; Rita Nurnaningsih; Zurlina Lubis; Eko Nur Hermansyah; Wahyuni Sri Astutik (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study investigates the differential impact of microfinance on household welfare in rural and urban areas of Indonesia through a quantitative comparative analysis. Employing data from the 2018 National Socioeconomic Survey (SUSENAS) covering 294,426 households across Indonesia's 38 provinces, this research utilizes binary logistic regression and propensity score matching to assess welfare outcomes. The findings reveal that microfinance access significantly improves household welfare indicators in both settings, with statistically significant stronger effects observed in rural areas (coefficient: 0.312, p<0.01) compared to urban areas (coefficient: 0.197, p<0.01). Rural households with microfinance access demonstrate a 29% increase in monthly income and 23% improvement in consumption expenditure, while urban households exhibit 17% and 14% increases respectively. The study identifies loan purpose, monthly income, interest rates, education level, and household size as significant predictors of welfare improvement. Results indicate that rural poverty rates decreased from 12.22% to 11.79%, while urban poverty declined from 7.29% to 7.09% between 2023-2024. These findings suggest that microfinance serves as a more effective poverty alleviation mechanism in rural contexts, primarily due to limited alternative financial access and higher vulnerability to income shocks. Policy implications emphasize the need for geographically differentiated microfinance strategies that account for rural-urban disparities in financial infrastructure, entrepreneurial ecosystems, and socioeconomic conditions.